The Effectiveness of Liquid Bio-Organic Fertilizer Water Hyacinth with Trichoderma Sp on The Growth and Productivity of Mustard Pakcoy, Mustard Petsai and White Mustrad - Febiayu Aloatuan; Centhya Victorin Maitimu (Jurnal Biologi Tropis, 2022)
Mustard is a vegetable with high economic value, including mustard pakcoy (Brassica rapa subsp, chinensis), mustard petsai (Brassica chinensis L), and white mustard (Brassica rapa subsp, pekinensis). To meet consumer needs, it is necessary to increase the production of mustard through organic farming by implementing an agricultural system that utilizes water hyacinth in the form of liquid organic fertilizer. Water hyacinth is an aquatic weed so an alternative is needed to reduce its population by using it as a liquid organic fertilizer with a bio-activator Trichoderma sp. The purpose of the study was to measure plant height, number of leaves, leaf width, and wet weight of mustard pakcoy, mustard petsai, and white mustard. The design of this study used a single factor RAL, namely giving water hyacinth POC with bio-activator Trichoderma sp on 3 types of mustard, with 3 levels, namely A = 32 ml/L (mustard pakcoy), B = 32 ml/L (mustard petsai), C=32 ml/L (white mustard) which was repeated 5 times. Research proves that giving water hyacinth POC with bio-activator Trichoderma sp 32 ml/liter has a significant effect on the height and width of white mustard leaves. For the number of leaves and wet weight, giving water hyacinth POC with bio-activator Trichoderma sp 32 ml/liter had a significant effect on mustard pakcoy compared to other mustards. This means that POC with bio-activator Trichoderma sp can be used as an environmentally friendly liquid organic fertilizer, especially for mustard pakcoy and white mustard which can stimulate plant growth and productivity.